SOCIAL-ECONOMIC AND IDEOLOGICAL FOUNDATONS OF MORALS IN THE ETHICAL HERITAGE OF EUGENE FEDORENKO - Yarmolitska, Nataliia; Moskalchuk, Maryna (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2021)
In the article are considered the main moral-ethical research ukrainian soviet philosophy E. Fedorenko. Based on the conducted theoretical reconstruction of scientific-research activity scientist was defined the direction his scientific research, this: the study of ethical problems from the history ethical teachings to relevant questions current life, development of methodological problems history-ethical researches, research work and moral-ethical enlightenment. From the analysis of scientific heritage E. Fedorenko was determined the basis moments his scientific activity, first of all, this investigation of occurrence and originality the theoretical ethic, research in the field social-economic and ideological basics moral and installation its relationship with others forms the social consciousness. He tried to find his own, special for scientific justification moral and designing ethics of the future perfect the soviet human. However, main merit E. Fedorenko, like most soviet scientists, there was an attempt to show, what domestic soviet ethics the gradually departs from inherent in it the ideological form soviet marxism, from moralistic philosophy.